2022
DOI: 10.3389/fphar.2022.890790
|View full text |Cite
|
Sign up to set email alerts
|

A Cyclic Disulfide Diastereomer From Bioactive Fraction of Bruguiera gymnorhiza Shows Anti–Pseudomonas aeruginosa Activity

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen that commonly causes hospital-acquired infection and is of great concern in immunocompromised patients. The quorum sensing (QS) mechanism of P. aeruginosa is well studied and known to be responsible for pathogenicity and virulence. The QS inhibitor derived from the natural product can be an important therapeutic agent for pathogen control. The present study reports the role of Bruguiera gymnorhiza purified fraction (BG138) in inhibiting virulence factor produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…The results indicated that PT22 may impede acylated homoserine lactone (AHL) production, resulting in QSI activity, and presents higher activity in reducing C4-HSL production. The endophytic fungus Bruguiera gymnorhiza purified fraction (BG138) interferes with the P. aeruginosa QS system, resulting in a decrease in QS signaling molecules and transcriptional levels of the QS-related genes ( Dahibhate et al., 2022 ). Similar results were found in which citrinin could downregulate the QS-related genes ( las I, las R, rhl I, and rhl R) and showed a QSI activity of P. aeruginosa ( Ji et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that PT22 may impede acylated homoserine lactone (AHL) production, resulting in QSI activity, and presents higher activity in reducing C4-HSL production. The endophytic fungus Bruguiera gymnorhiza purified fraction (BG138) interferes with the P. aeruginosa QS system, resulting in a decrease in QS signaling molecules and transcriptional levels of the QS-related genes ( Dahibhate et al., 2022 ). Similar results were found in which citrinin could downregulate the QS-related genes ( las I, las R, rhl I, and rhl R) and showed a QSI activity of P. aeruginosa ( Ji et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The growth curves measurement assays were performed according to the reported methods with some modifications ( Dahibhate et al., 2022 ). Overnight cultures of P. aeruginosa PAO1 were inoculated into 5 mL fresh LB broth with 0.1% volume percent and supplemented with different concentrations of PT22 (0.50 mg/mL, 0.75 mg/mL, 1.00 mg/mL, and 2.00 mg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…The diversity of diterpenoids in plants playing important roles in plant development, stress resistance, and interactions with environmental microorganisms, depends on the various skeletons biosynthesized by terpene synthases and the substrate promiscuity of cytochrome P450 monooxygenases (P450s), along with other postmodification enzymes [38]. In the genus Bruguiera, researchers have isolated five different skeletal types of diterpenoid (Table 2 and Figure 3), namely ent-pimarane (79-82), isopi-marane (83)(84), ent-beyerane (85-86), ent-kaurane (62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78), and ent-gibberellane (59-61), with the key intermediate pimarane in their biosynthesis. Most sesterpenoids are sourced from marine organisms, with approximately 15% of these compounds having been isolated from plants [44].…”
Section: Diterpenoidsmentioning
confidence: 99%
“…Previous research indicates that sulfides play a crucial role in plant defense against various pathogens and pests [73]. Dahibhate et al [74] discovered that a mixture of brugierol and isobrugierol exhibited inhibitory activity against Pseudomonas aeruginosa by reducing the formation of virulence biofilms controlled by the quorum sensing system, lowering the level of virulence factors, thereby attenuating the pathogenicity of the bacterium against Bruguiera plants. Simultaneously, Zhang et al [21,75] cultured and isolated the endophytic fungus C. cladosporioides MA-299 from the leaves of B. gymnorrhiza, obtaining seven sulfur-containing 12-membered macrocyclic lactones (179)(180)(181)(182)(183)(184)(185).…”
Section: Sulfidesmentioning
confidence: 99%